(RE)Imagining and (RE)Calibrating community engagement professionals' roles in higher education. Issue 195 (5th May 2022) - Farmer‐Hanson, Ashley J.; Echols, Melisa A.; Nelson, Mark S.; Manning‐Ouellette, Amber
Abstract: Civic learning and democratic engagement (CLDE) work has become a central piece of higher education's mission, woven in daily tasks. This chapter explores how the community engagement professional (CEP) role can be reimagined across institutions and the opportunities, challenges, and next steps for moving forward. The strategic positioning of CEP's roles within the institution, provides opportunity and crucial pathways for college student development. Higher education has the opportunity to change national discourse on CLDE work and model how institutions play a significant role in building a democratic society.